Predation capacity of phytoseiid mites (Mesostigmata: Phytoseiidae) from Brazil on eggs of Diaphorina citri (Hemiptera: Liviidae) - Jiménez, S. [UNESP]; Rueda-Ramírez, D.; Moraes, G. J. de (Springer Nature, 2021)
The Asian citrus psyllid Diaphorina citri Kuwayama (Hemiptera: Liviidae) is a key vector of the causal agents of huanglongbing (HLB) in important citrus production regions of the world. The objective of this study was to estimate the predation capacity of mites of the family Phytoseiidae on eggs of that insect. Populations of 13 phytoseiid species were collected from five Brazilian states, to evaluate their predation capacity and ability to survive when fed with eggs of D. citri. Each predator was fed daily with 10 eggs of the insect. Predation rate was higher for Amblyseius herbicolus (Chant) collected in Botucatu (São Paulo state) and Pirenópolis (Goiás state) (respectively 4.7 and 2.9 eggs/female/day). Those populations also had high survivorship within the observation period of five days (4.8–5.0 days). These results are comparable to studies previously conducted by other authors with other phytoseiid species. Given the common occurrence of A. herbicolus on citrus, it seems possible that it may exert some effect on the population of D. citri under field condition. It seems worthwhile to conduct complementary studies to determine the feasibility of using this predator for the control of that insect.
Keywords: Biological control; Citrus; Eating habits; Life styles; Predators